Self Direct Learning Readiness in The Implemention of the E-Learning Method During the Covid-19 Pandemic Period for Medical Students 2018 Malahayati University - Enggari Setia Putri; Vira Sandayanti; Enggari Setia Putri; Devita Febriani Putri (Green Publisher Indonesia, 2021)
Since the 2019 Coronavirus Disease Pandemic (COVID-19) spread to Indonesia, the Ministry of Education and Culture (Kemendikbud) has asked all universities to implement a Home Learning system or study at home that utilizes learning media such as Electronic Learning (E-learning), thus there has been a change learning systems from conventional systems to online learning or E-learning. The purpose of this research is to find out how self-learning readiness is in the implementation of the E-learning method during the COVID-19 pandemic for the 2018 Malahayati University Medical Students. This type of research is quantitative with a descriptive design. The subjects of this study were all students of the Medical Study Program at the Faculty of Medicine, Malahayati University, batch 2018. The measuring instrument used was Self Directed Learning Readiness (SDLR) with the E-Learning method. The results of this study indicate that of the 150 respondents of the 2018 Malahayati University Medical Student with a high SDLR level of 138 people (92%) consisting of 96 female respondents and 42 male respondents and respondents with SDLR levels. 12 people (8%) consisting of 8 female respondents and 4 male respondents. The conclusion is that it is known that the 2018 Malahayati University Medical Students have a high SDLR level with the E-Learning method or can be said in the ready category.